Differentiation of stem cells from human deciduous and permanent teeth into spiral ganglion neuron-like cells. (April 2018) - Gonmanee, Thanasup; Thonabulsombat, Charoensri; Vongsavan, Kutkao; Sritanaudomchai, Hathaitip
Highlights: DPSC and SHED can differentiate into SGN cells. The differentiated cells exhibit SGN-specific markers and its functional activity. SGNs Plasticity is similar between DPSC and SHED. DPSC and SHED appear to be alternative source to treat patients with hearing loss. Abstract: Objective: Stem cells from pulp tissue are a promising cell-based therapy for neurodegenerative patients based on their origin in the neural crest. The aim of this study was to differentiate and evaluate the ability of human dental pulp stem cells from permanent teeth (DPSC) and stem cells from human exfoliated deciduous teeth (SHED) to differentiate into spiral ganglion neurons. Design: After isolation and characterization of mesenchymal stem cell properties, DPSC and SHED were treated with the neurotrophins brain-derived neurotrophic factor (BDNF), neurotrophin-3 (NT-3), and glial cell-derived neurotrophic factor (GDNF). The differentiation was identified by immunostaining and qRT-PCR analysis of neuronal markers and measuring intracellular calcium activity. Results: After 2 weeks of induction, morphological changes were observed in both DPSC and SHED. The differentiated cells expressed neuron-specific class III beta-tubulin, GATA binding protein 3 (GATA3) and tropomyosin receptor kinase B, protein markers of spiral ganglion neurons. These cells also showed upregulation of the genes encoding these proteins, namely GATA3 and neurotrophic receptor tyrosine kinase 2. Intracellular calcium dynamics that reflect neurotransmitter release were observed in differentiated DPSC and SHED. Conclusion: These results demonstrate that dental pulp stem cells from permanent and deciduous teeth can differentiate into spiral ganglion neuron-like cells.